Prevalence and associated risk factors with malnutrition among under-five Nepalese children of Borbote village, Ilam - Niraula, SR; Barnwal, SP; Paudel, S; Mishra, S; Dahal, S; Das, S; Pradhan, S; Ghimire, S; Khanal, S; Sharma, S; Rajput, S; Bhattarai, S; et al. (Health Renaissance, 2013)
Background: Malnutrition is a major public health & nutrition problem in Nepal. It is associated with many risk factors like low birth weight, multiple birth, short spaced birth, extra diet, and iron supplementation in pregnancy etc. Objectives: This study aims at finding out the nutritional status of under-five Nepalese children of Borbote village, Ilam and risk factors associated with malnutrition. Methods: A cross sectional study was conducted in Borbote village, Ilam. A total of 186 under-five children was selected by purposive sampling. Non parametric test was applied to find out statistical significance. Logistic regression method was used to identify the factors influencing the malnutrion. Results: According to WHO, 20% children were malnourished . of which 14% were moderately undernourished and 6% were severely undernourished. Mothers exclusively breast feeding for 6 months had only 20.0% low weight for age children and those who didn.t had 34.8% (P=0.041). Pregnant ladies who took iron supplements had 20.5% of low weight for age children compared to 37.1% (P =0.037) in those who didn.t take supplements. Malnutrition was found more in those who were below poverty line 27.94% (P=0.023) compared to those above poverty line 12.00%. Conclusion: Significant number of under-five children of Bortbote village was malnourished. Maternal factors have significant association with nutritional status of the children which include extra diet in pregnancy and lactation, iron supplements in pregnancy, exclusive breast feeding for six months. Extra attention should be provided by the Ministry of Health towards maternal and child health. Health Renaissance, January-April 2013; Vol. 11 No.1; 111-118 DOI: http://dx.doi.org/10.3126/hren.v11i2.8217